2021
DOI: 10.3390/molecules26123692
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Effect of Tea Polyphenols on the Regulation of Intestinal Flora

Abstract: Tea polyphenols (TPs) are the general compounds of natural polyhydroxyphenols extracted in tea. Although a large number of studies have shown that TPs have obvious neuroprotective and neuro repair effects, they are limited due to the low bioavailability in vivo. However, TPs can act indirectly on the central nervous system by affecting the “microflora–gut–brain axis”, in which the microbiota and its composition represent a factor that determines brain health. Bidirectional communication between the intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 160 publications
0
24
0
Order By: Relevance
“…Tea polyphenols are generally recognized as strong antioxidants because of its special molecular structure, and their antioxidant action has been suggested to contribute to the alleviation of metabolic syndrome. Tea flavanols (such as catechin and epicatechin) inhibited the growth of several pathogens and have an inhibitory effect on the growth of symbiotic anaerobes [ 9 ]. EGCG, an active polyphenolic catechin of tea, which is the most abundance of green tea, plays a major role in the role of antioxidant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tea polyphenols are generally recognized as strong antioxidants because of its special molecular structure, and their antioxidant action has been suggested to contribute to the alleviation of metabolic syndrome. Tea flavanols (such as catechin and epicatechin) inhibited the growth of several pathogens and have an inhibitory effect on the growth of symbiotic anaerobes [ 9 ]. EGCG, an active polyphenolic catechin of tea, which is the most abundance of green tea, plays a major role in the role of antioxidant.…”
Section: Discussionmentioning
confidence: 99%
“…However, different types of tea seemed to have different impacts on lipid metabolism. Reports showed that TPs can affect the central nervous system by through the “microflora–gut–brain axis,” in which the microbiota and its composition determines brain health [ 9 ]. A study compared the antiobesity efficiency of different tea types found that white tea, yellow tea, and blue tea increased the carnitine palmitoyltransferase-I (CPT-1) level, while white tea, green tea, and raw Pu-erh tea (a kind of dark tea) decreased the fatty acid synthase (FAS) level [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al described that Gastrointestinal microbiota has an impact on metabolic activities and indeed the bioavailability for total polyphenols in the body, which is crucial in neurodegenerative illnesses [7]. The somatic mutation and recombination test revealed that two separate antineoplastic cancer medications as streptozotocin and cyclophosphamide had genotoxic effects in somatic cells.…”
Section: White Teamentioning
confidence: 99%
“…In the long process of evolution of gut microbiota, through individual adaptation and natural selection, the microbiota of different species, microbiota and host, microbiota and host environment are always in a state of dynamic balance, forming an interdependent system. More and more evidences show that gut microbiota plays a key role not only in the metabolism of nutrients and drugs and the absorption of fat in the diet, but also in the regulation of immunity, physiology, metabolism, and health maintenance ( Xi et al., 2021 ; Zhang et al., 2021 ). Besides, intestinal microorganisms could affect multiple tissues and organs, such as intestinal cells, liver, adipose tissue, brain, and muscle.…”
Section: Introductionmentioning
confidence: 99%